Human nature: neither material nor spiritually being - M. Alba Martínez Amorós (Pensamiento. Revista de Investigación e Información Filosófica, 2017)
The idea of «human nature» defended by Ortega y Gasset is as original as opposite to what is usually understood. We are making a mistake if the starting point is to conceive Man as one living being among others. Neither science nor philosophy, while remaining in the Eleatic tradition, can give a clear explanation. Science, because if we look at Man, as he is presented to us, it is impossible to distinguish in him materially from spiritually; his body and his psyche. Philosophy, because the concept of «human nature» is an invention of our reason, a fantasy. That nature doesn’t exist because the being of man is so strange and different from other beings that its consistency is just going to be what it never manages to be. Therefore, it is what happens, a journey, a history that is running within a circumstance. This is my life, and that of everyone.